Stunting and future risk of obesity: principal physiological mechanisms - Sawaya Ana Lydia; Roberts Susan (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
There is a fair amount of epidemiological evidence showing that nutritional stunting causes increased risks of obesity. Obesity is increasing dramatically not only in developed countries but also in developing countries, such as Brazil, especially among the poorer. The mere coexistence of undernutrition and obesity among poor people has a great impact, as the burden in the social, economic, and health care systems is remarkable. In addition, an increasing number of studies have shown that nutritional stunting causes a series of important long-lasting changes such as lower energy expenditure, higher susceptibility to the effects of high-fat diets, lower fat oxidation, and impaired regulation of food intake. These findings suggest that a broader and more detailed understanding of the long-lasting effects of early undernutrition, direct cause of nutritional stunting, is needed. Within this context, we present data of some physiological mechanisms that substantiate the association between previous undernutrition and future obesity.